2007
DOI: 10.1056/nejmc071528
|View full text |Cite
|
Sign up to set email alerts
|

JAK2V617F Mutation in Unexplained Loss of First Pregnancy

Abstract: Byrne MJ, Nowak AK. Modified RECIST criteria for assessment of response in malignant pleural mesothelioma. Ann Oncol 2004;15:257-60. Juweid ME, Cheson BD. Positron-emission tomography and assessment of cancer therapy. N Engl J Med 2006;354:496-507. Ceresoli GL, Chiti A, Zucali PA, et al. Early evaluation in malignant pleural mesothelioma by positron emission tomography with [18F] fluorodeoxyglucose. J Clin Oncol 2006;24:4587-93. Carretta A, Landoni C, Melloni G, et al. 18-FDG positron emission tomography in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
1
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 5 publications
2
23
1
4
Order By: Relevance
“…The presence of high incidence of thromboembolic attacks due to JAK2V617F gene mutation and pregnancy loss in obese women and a possible relationship between these parameters is a matter of concern. In this study women who were positive for JAK2V617F mutation in the case group represented 9.3 % versus the control group who were negative for mutation (p<0.001) Mercier et al, (2007) supported this results that the mutation was present more frequently in patients with past history of pregnancy loss (1.06%) than in control group (0.20%). Also Melillo et al, (2009) stated that fetal loss encountered more in females with the JAK2 V617F mutation (mutated vs. unmutated: 36.0% vs. 8.3%, P< 0.037), and this correlation was further confirmed by multivariate analysis (OR: 6.19; 95% CI: 1.17-32.61, P < 0.038).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The presence of high incidence of thromboembolic attacks due to JAK2V617F gene mutation and pregnancy loss in obese women and a possible relationship between these parameters is a matter of concern. In this study women who were positive for JAK2V617F mutation in the case group represented 9.3 % versus the control group who were negative for mutation (p<0.001) Mercier et al, (2007) supported this results that the mutation was present more frequently in patients with past history of pregnancy loss (1.06%) than in control group (0.20%). Also Melillo et al, (2009) stated that fetal loss encountered more in females with the JAK2 V617F mutation (mutated vs. unmutated: 36.0% vs. 8.3%, P< 0.037), and this correlation was further confirmed by multivariate analysis (OR: 6.19; 95% CI: 1.17-32.61, P < 0.038).…”
Section: Discussionsupporting
confidence: 84%
“…(El Hachem et al, 2017) It is recorded that the disorders which promote to venous thrombosis, are all named "thrombophilias," which have a role in the pathogenesis or the process of fetal loss. The great differences between theories as well as keeping in mind the correlation between such disorders and unexplained pregnancy loss suggests the presence of underlying risk modifiers (Mercier et al ., 2007). The included women in the present study had at least one history of live birth, to rule out any anatomical factor that might be a cause for the repeated losses.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, in that study no exhaustive list of risk factors for pregnancy loss was provided in 159 (41%) of the included women. In contrast to our observation, a large previous study found a prevalence of 1% in women with a single unexplained pregnancy loss [5]. However, the positive test results in that study were not confirmed by repeated analyses.…”
contrasting
confidence: 99%
“…In vitro gene promoter studies identified functional HNF4a binding sites near the genes encoding human procoagulant factors (F) II (F2), VII (F7), VIII (F8), IX (F9), X (F10), XI (F11), XII (F12) [1][2][3][4][5][6][7], and anticoagulant factors protein S (PROS1), protein Z (PROZ) and antithrombin III (SERPINC1) [8][9][10]. The in vivo importance of HNF4a in regulating hepatic transcription of procoagulant genes was established by examining hepatic mRNA levels from liver-specific HNF4a-null mice [11].…”
Section: Disclosure Of Conflict Of Interestsmentioning
confidence: 99%
“…The presence of polymorphism V617F G4T in Janus kinase 2 gene JAK2 among the studied SNP is due to the data on a higher frequency pregnancy interruptions caused by thrombosis in women with this mutation [88,89]. However, somatic type of mutation, a clear correlation with age and the low enough prevalence [90] is hardly allow us to speak about the effectiveness of this SNP testing in preparation for IVF.…”
Section: Snps In the Renin-angiotensin Systemmentioning
confidence: 94%